Relationship between bases of power and job stresses : role of mentoring - May-Chiun, Lo; Ramayah, Thurasamy; Wei, Tak Liew (SpringerLink, 2014)
Building upon the social exchange theory, this paper hypothesized the direct effect of bases of power on job stress with mentoring as moderator. Power bases and job stresses were conceptualized as 7- and 3- dimensional constructs, respectively. One hundred and ninety-five Malaysian managers and executives working in large-scale multinational companies participated in this study. The results have indicated that bases of power as possessed by supervisors have strong effect on employees’ job stress and mentoring was found to have moderated the relationship between power bases and job stress. Implications of the findings, potential limitations of the study, and directions for future research were discussed further.